Transdiagnostic Role of Glutamate and White Matter Damage in Neuropsychiatric Disorders: A Systematic Review - I. Luttenbacher; A. Philips; R. Kazemi; A. Hadipour; I. Sanghvi; J. Martinez; M. Adamson (European Psychiatry, 2022)
Introduction Neuropsychiatric disorders including Generalized Anxiety Disorder (GAD), Obsessive-Compulsive Disorder (OCD), Major Depressive Disorder (MDD), Bipolar Disorder (BD), and Schizophrenia (SZ) have been considered distinct categories of diseases despite their overlapping characteristics and symptomatology.